2017
DOI: 10.1002/kin.21130
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oxygenated Molecules from Atmospheric Autoxidation of Hydrocarbons: A Prominent Challenge for Chemical Kinetics Studies

Abstract: Recent advances in chemical ionization mass spectrometry have allowed the detection of a new group of compounds termed highly oxygenated molecules (HOM). These are atmospheric oxidation products of volatile organic compounds (VOC) retaining most of their carbon backbone, and with O/C ratios around unity. Owing to their surprisingly high yields and low vapor pressures, the importance of HOM for aerosol formation has been easy to verify. However, the opposite can be said concerning the exact formation pathways o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…Due to their high O/C ratios (close to unity), they have sufficiently low volatilities to contribute to aerosol nucleation and growth. Several studies have quantified HOM yields from monoterpenes (Ehn et al, ; Ehn et al, ; Jokinen et al, ), isoprene (Jokinen et al, ), and AVOCs (e.g., alkyl benzenes; Molteni et al, ; Praske et al, ; S. Wang et al, ). The exact formation pathways and properties of HOMs are still under investigation (Berndt et al, ; Bianchi et al, ; Ehn et al, ).…”
Section: Nucleation and Growth Mechanisms: New Results From Laboratormentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their high O/C ratios (close to unity), they have sufficiently low volatilities to contribute to aerosol nucleation and growth. Several studies have quantified HOM yields from monoterpenes (Ehn et al, ; Ehn et al, ; Jokinen et al, ), isoprene (Jokinen et al, ), and AVOCs (e.g., alkyl benzenes; Molteni et al, ; Praske et al, ; S. Wang et al, ). The exact formation pathways and properties of HOMs are still under investigation (Berndt et al, ; Bianchi et al, ; Ehn et al, ).…”
Section: Nucleation and Growth Mechanisms: New Results From Laboratormentioning
confidence: 99%
“…Several studies have quantified HOM yields from monoterpenes Ehn et al, 2017;Jokinen et al, 2015), isoprene , and AVOCs (e.g., alkyl benzenes; Molteni et al, 2018;Praske et al, 2018;. The exact formation pathways and properties of HOMs are still under investigation (Berndt et al, 2016;Bianchi et al, 2019;Ehn et al, 2017). Schobesberger et al (2013) have shown that HOMs (e.g., C 10 H 12-16 O 2-10 ) formed from OH oxidation reactions of pinanediol (C 10 H 18 O 2 , a first generation oxidation product of monoterpenes) interact with sulfuric acid to form monomers to tetramers ( Figure 4), and these HOMs can enhance J for sulfuric acid.…”
Section: Homs Formed From Vocs Oxidation Reactionsmentioning
confidence: 99%
“…Evidence for the operation of peroxy radical isomerization reactions has been reported in numerous theoretical and laboratory studies (e.g. Vereecken and Peeters, 2004;Peeters et al, 2009;Crounse et al, 2013;Ehn et al, 2014;2017;Jokinen et al, 2014;Rissanen et al, 2015;Jørgensen et al, 2016), and new information is constantly emerging on this important aspect of peroxy radical chemistry. The present 10 section provides a summary of selected classes of isomerization reaction that are currently being considered and represented in ongoing mechanism development work.…”
Section: Unimolecular Reactions Of Ro 2 Radicalsmentioning
confidence: 98%
“…These reactions therefore potentially play an important role in HO x radical recycling under NO xlimited conditions, and in rapid chain oxidation mechanisms generating highly oxidised multifunctional molecules, HOMs (e.g. Peeters et al, 2009;Crounse et al, 2013;Ehn et al, 2014;2017;Jokinen et al, 2014;Rissanen et al, 2015). The relative contributions of the various reactions available for RO 2 thus influence the distribution and functional group content 30 of the oxidized products formed, and their physicochemical properties (e.g.…”
mentioning
confidence: 99%
“…These "non-HOM" RO2 radicals may then also be key molecules for determining the final branching leading to the different observed HOM with 7 or more O atoms. This may shed light on one of the main open challenges (Ehn et al, 2017) in understanding HOM formation, namely how RO2 radicals with e.g. 6, 8 and 10 O atoms can form within a second, yet the relative distribution of these three does not change if the reaction time is allowed to increase (Berndt et al, 2015).…”
Section: Yield Estimation and Temperature Influence For Molecule-specmentioning
confidence: 99%